The acute effects of working time patterns on fatigue and sleep quality using daily measurements of 6195 observations among 223 shift workers - Hardy A van de Ven; Gerben Hulsegge; Thijmen Zoomer; Elsbeth M de Korte; Alex Burdorf; Karen M Oude Hengel (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVES: This study aimed to estimate acute effects of roster characteristics on fatigue and sleep quality and investigated whether these effects differed by individual characteristics. METHODS: Using an ecological measurement assessment survey, fatigue and sleep quality were daily measured among 223 shift workers for up to eight weeks. A questionnaire assessed baseline characteristics, and roster data were retrieved from the company registers to determine roster parameters. The effects between each shift parameter on fatigue and sleep quality were estimated with random- and fixed-effects models. RESULTS: Compared to day shifts, night shifts were related to fatigue [β=0.22; 95% confidence interval (CI) 0.05-0.39] and poorer sleep quality (β=0.64; 95% CI 0.47-0.80), and more successive night shifts with more fatigue (up to β=0.68; 95% CI 0.49-0.87 for ≥2 nights). Fatigue was increased after a quick return (<11 hours) (β=1.94; 95% CI 1.57-2.31) or 11-16 hours (β=0.43; 95% CI 0.26-0.61) compared to >16 hours between shifts. Compared to forward rotation, stable (β=0.22; 95% CI 0.01-0.43) and backward rotation (β=0.49; 95% CI 0.23-0.74) were also associated with more fatigue. Workers with a morning or intermediate chronotype had poorer sleep quality after a night shift, while workers with poor health reported poor sleep quality as well as more fatigue after a night shift. CONCLUSIONS: To alleviate acute effects of shift work on fatigue, shift schedules should be optimized by ensuring more time to recover and rotate forwards.